Maths alive! : INSET mathematics for the National Curriculum (Key stages 1, 2, 3) - Biggs, Edith Ethel; Shaw, Kathleen (London ; New York : Cassell, 1995)
Designed for all teachers at primary, middle and lower-secondary level who have to understand and implement the UK National Curriculum for Mathematics at Key Stages 1 to 3, this book contains activities that should help pupils achieve their maximum potential in the various areas of mathematics.
BIED
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Mathematics teachers -- In-service training -- Great Britain